Alzheimer's Disease-like Paired Helical Filament Assembly from Truncated Tau Protein Is Independent of Disulfide Crosslinking. Issue 23 (24th November 2017) - Al-Hilaly, Youssra K.; Pollack, Saskia J.; Vadukul, Devkee M.; Citossi, Francesca; Rickard, Janet E.; Simpson, Michael; Storey, John M.D.; Harrington, Charles R.; Wischik, Claude M.; Serpell, Louise C.
Abstract: Alzheimer's disease is characterized by the self-assembly of tau and amyloid β proteins into oligomers and fibrils. Tau protein assembles into paired helical filaments (PHFs) that constitute the neurofibrillary tangles observed in neuronal cell bodies in individuals with Alzheimer's disease. The mechanism of initiation of tau assembly into PHFs is not well understood. Here we report that a truncated 95-amino-acid tau fragment (corresponding to residues 297–391 of full-length tau) assembles into PHF-like fibrils in vitro without the need for other additives to initiate or template the process. Using electron microscopy, circular dichroism and X-ray fiber diffraction, we have characterized the structure of the fibrils formed from truncated tau for the first time. To explore the contribution of disulfide formation to fibril formation, we have compared the assembly of tau(297–391) under reduced and non-reducing conditions and for truncated tau carrying a C322A substitution. We show that disulfide bond formation inhibits filament assembly and that the C322A variant rapidly forms long and highly ordered PHFs. Graphical Abstract: Image 1 Highlights: Truncated tau is a major component of paired helical filaments (PHF) in neurofibrillary tangles in Alzheimer's brain tissue and encompasses the core structure of PHF isolated from Alzheimer's disease brain. Truncated tau (297–391) forms filaments that share fine structural characteristics with isolated PHF. Reduction of the disulfide, or replacement of Cys with Ala in truncated tau, leads to enhanced filament formation. Truncated unmodified tau is sufficient for the assembly of PHF found in Alzheimer's disease.